IMPLEMENTASI ANALISIS JABATAN DALAM RANGKA MENYIAPKAN ORGANISASI AKAMIGAS MENUJU â€œSTEM â€œAKAMIGASâ€ (Studi pada Akademi Minyak dan Gas Bumi, Cepu, Jawa Tengah) - Yunanik, Yunanik (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2013)
This case study aims to understand the implementation of job analysis and do job analysis correctlyÂ and objectively, real, transparent, also comprehensiveÂ and completeÂ on all job information in order to prepare the Akamigas organizationÂ towardÂ STEM â€œAkamigasâ€.Â Â This materials case study is consisted by the results of job analysis; they are job description and the job specification.Â In addition,Â this case study also illustratesÂ the constraints which are faced in the implementation of the results of job analysis.This studyÂ is a qualitativeÂ research,Â whereÂ the data collectionÂ is done through observation, interviews,Â and documentationÂ study, also obtains informationÂ throughÂ the Forum Group DiscussionÂ (FGD) with intent to obtain the results of objective interpretation, so it is able to explore more about the Job Analysis ImplementationÂ in order to prepare the organization AkamigasÂ towardÂ STEM â€œAkamigasâ€.Â The resultsÂ of data collectionÂ were analyzed by qualitative methods using descriptive paradigm. Phenomenological approach which is reinforced by ethnography to find insight that is used to describeÂ a deep understandingÂ on the implementation of the analysis by the existing positions.The findingsÂ of this study indicate; generally, the results of job analysis that ideal has not been achieved, althoughÂ the employees and leaders understand the significance of job analysis. There are someÂ errorsÂ in the implementation of job analysis, includingÂ process, implementation,Â evaluation position,Â individual assessment, development training, job competency,Â lack of human resources at this time, lack of communication that caused the problem.Â Furthermore, analyzing all job information toward organization of STEMÂ â€œAkamigasâ€ throughÂ a study that is systematicallyÂ and regularly collectingÂ all the informationÂ and facts that relate to a position. The result of study indicate; (1) there are job description which have not been included in old job analysis. (2) there is a change in the organizational structure of college that affect change in the echelon, number of position avalaible and nomenclature changes of organizational units.